Distance Education in Higher Education: The Perspective of Key Social Actors - Zaborova, Elena; Markova, Tatiana (KnE Social Sciences, 2021)
This article considers the perspective of the key social actors (students, teachers and university management) regarding distance education development in Russia. In the modern information and digital age, distance education – based on the possibility of disseminating knowledge through modern computer technologies – is being actively introduced into the Russian higher education system. The pace of implementation is increasing in Russia, yet its assessment as a new form of learning and teaching is ambiguous. There are clear advantages to this form when compared with traditional face-to-face classroom instruction including: the accessibility of education to a wide audience; the possibility to earn a degree irrespective of place of residence; variability of learning time selection; relatively low tuition fees. At the same time, however, many believe that the quality of education received by distance students is lower than that received via face-to-face teaching, due to both the lack of student’ readiness and the difficulties related to pedagogical process organization and management. This study considers whether distance higher education will continue to develop in Russia. The answer to this question depends to a large extent on the perspective of the key social actors. The study analyses their attitudes to distance education and make the following conclusions: 1) University management generally accept this form because of its economic advantage and attitudes of the higher education authorities. Students also vote in favour, because it allows them to earn a degree without giving up work, family and home-related commitments. The most negative assessment is given by teachers who conduct classes at a distance and can compare distance learning outcomes with those in the traditional face-to-face classroom instruction. Keywords: distance education, quality of education, social actors, students, teachers, university management